Study, Design, Modeling, Simulation, and Control Analysis of AC-AC Power Converters - Salam Waley Shneen (Peneliti Teknologi Teknik Indonesia, 2025)
The current study aims to provide an analysis of the performance of the AC power converter by constructing a simulation model. A preliminary simulation model is designed to identify the behavior of open-loop and closed-loop systems. To improve the converter's performance, pulse width modulation (PWM) technology and a conventional controller are used to control the converter's output voltage and frequency. An AC converter varies electrical quantities to suit the load requirements and the available power source. Converters can be used in lighting circuits to control the intensity of lighting and to control the rotational speed of electric motors, such as single-phase induction motors. The power electronics converter model is an AC voltage control unit type, built using electronic switches, which are semiconductor devices such as thyristors and transistors (IGBT, MOSFET). The input terminal of the converter is connected to a constant voltage and frequency AC power supply, while the output terminal is connected to an AC load, controlled by the root mean square value of the AC voltage. The output of the converter can be controlled by regulating the operating periods of the electronic switches, depending on the type and method of connecting the switches, whether full wave or half wave, with regulated periods. The study presents a test of AC converter, and through simulation results, it is shown that the converter's performance can be improved using pulse width modulation technology and a conventional PID controller. Modeling a single-phase AC transformer system using a thyristor as an electronic switch. The system model consists of a 100V, 50Hz single-phase power supply connected in series with a transformer containing two thyristor switches connected in parallel. The transformer output is connected to a load with a resistance of 10 ohms. Tests were proposed using single-phase converter simulation models, where the switching angle of the electronic thyristor was changed from 10 to 90 degrees in 10-degree increments. The simulation results showed that the converter's output voltage could be changed by changing the switching angle, with the change being inverse; that is, increasing the switching angle leads to a decrease in the converter's output voltage.